Multiwalled Carbon Nanotube Purification Probed by Electrochemistry: Low‐Temperature Chlorine Gas Treatment Meets High‐Temperature Annealing. Issue 10 (18th August 2022) - Berrada, Nawal; El Housseini, Wassim; Desforges, Alexandre; Gleize, Jérôme; Ghanbaja, Jaafar; Etienne, Mathieu; Houllé, Matthieu; Bellouard, Christine; Vigolo, Brigitte
Abstract: The metal‐based residues in carbon nanotube samples can have an enormous impact to their properties which hinders their transfer to practical applications. Development of high‐performance purification methods and high sensitive approaches to detect and quantify the remaining impurities within the nanotube samples are still an active research field. Here, commercial multiwalled carbon nanotubes have been purified thanks to a non‐standard one‐step gas phase treatment using chlorine. Its facile reaction with the metal based impurities located inside and outside the carbon nanotubes allows to efficiently remove them at 1000 °C, with a sample yield of 79%. Raman spectroscopy and X‐ray photoelectron spectroscopy show that the carbon nanotube quality is preserved after purification. The quantity of magnetic residues is accurately evaluated by magnetic measurements, their outcome content is below 500 ppm (weight %). Finally, the redox behavior probed with hydrogen peroxide reduction is competitive with that obtained with a commercial sample thermally purified at 2400 °C. These two techniques were combined for the first time for high sensitivity characterization of ultra‐pure multiwalled carbon nanotubes. The used chlorine‐based treatment fulfills the requirements of an alternative tool to develop low energy processes for large scale industrial production of purified carbon nanotubes. Abstract : Ultra‐pure MWCNTs have been prepared by means of a low energy consumption using chlorine. Unprecedented, magnetic and electrochemical measurements have been combined to ascertain the quasi complete removal of metallic impurities from MWCNt samples.